A data driven approach for positive electronic word-of-mouth in management education - Kapse, Manohar; Sinha, Anamika; Sharma, Vinod; Poulose, Jeanne (London : SAGE Publications: SAGE Business Cases Originals, 2023)
This case equips students to generate a hypothesis, test it by choosing appropriate statistical tests, calculate the statistical tests using R software, and interpret the outcome to develop strategies in decision making. Often decisions in favor of attending a management institute are made in the absence of complete data, or based on biased or false claims made by various stakeholders whether they be institutes, students, or self-appointed rating agencies. This case brings forth the merit of data-backed decisions where claims about graduates' average starting salary, and the impacts of gender and prior work experience on starting salary, can be studied and assumptions can be questioned. The case touches upon the pertinent issue of the influence of negative electronic word-of-mouth (eWoM) on the brand image of a business school and raises the dilemma faced by top management caught between the claims and counterclaims made by disgruntled students and placement committees.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Communication in management; School management and organization -- Case studies; Decision making